2023
DOI: 10.1186/s40793-023-00469-x
|View full text |Cite|
|
Sign up to set email alerts
|

Potato root-associated microbiomes adapt to combined water and nutrient limitation and have a plant genotype-specific role for plant stress mitigation

Abstract: Background Due to climate change and reduced use of fertilizers combined stress scenarios are becoming increasingly frequent in crop production. In a field experiment we tested the effect of combined water and phosphorus limitation on the growth performance and plant traits of eight tetraploid and two diploid potato varieties as well as on root-associated microbiome diversity and functional potential. Microbiome and metagenome analysis targeted the diversity and potential functions of prokaryot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 96 publications
1
14
0
Order By: Relevance
“…For microbiomics analysis, sampling was done on separate levels (soil, peel, peripheral tissue and inner tissue of the beet root); however, for this case study, these four levels were merged to reduce the analytical complexity. We followed a standard bioinformatics workflow as described [ 55 ]. The resulting ASV table represents the microbiomics input datasets in this case study.…”
Section: Resultsmentioning
confidence: 99%
“…For microbiomics analysis, sampling was done on separate levels (soil, peel, peripheral tissue and inner tissue of the beet root); however, for this case study, these four levels were merged to reduce the analytical complexity. We followed a standard bioinformatics workflow as described [ 55 ]. The resulting ASV table represents the microbiomics input datasets in this case study.…”
Section: Resultsmentioning
confidence: 99%
“…Streptomyces, a dominant genus in soil microbiomes, has been associated with drought stress and plant health in dry environments [63][64][65]. The genus Occallatibacter showed depletion under drought conditions and was considered an important feature for the prediction of drought stress, although further research is needed to understand its specific impact on soil metagenomes under drought, as it has only been observed under heat stress and no-stress conditions [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Through the determination of specific conditions and combinations of factors, a microbiome could be reshaped to suppress specific kinds of pathogens. Emerging insights have been gained to monitor rhizosphere-associated microbes through plant responses to abiotic stresses ( Faist et al., 2023 ). Recent findings revealed that the plant adjusts nutrient availability and rhizosphere pH to monitor microbial recruitment and immune homeostasis ( Liu et al., 2023 ).…”
Section: Emerging Strategies For Shaping Rhizosphere Microbiomementioning
confidence: 99%